Psychological Distress Among Cancer Patients During COVID-19 Pandemic in the World: A Systematic Review - Momenimovahed, Zohre; Salehiniya, Hamid; Hadavandsiri, Fatemeh; Allahqoli, Leila; Günther, Veronika; Alkatout, Ibrahim (Frontiers in Psychology, 2021)
Aim: Patients with malignancies, experience high rates of psychological distress. Fear of Corona-infection combined with the interruptions in some treatment programs might affect the psychological health of cancer patients. This review study was conducted to investigate the psychological distress among cancer patients during COVID-19 pandemic to offer system-adapted individual solutions. Materials and methods: To identify the psychological distress of cancer patients, a comprehensive search was carried out in PubMed, Web of Science, and Scopus. English language and original articles were included in this study. Articles that addressed any psychological distress among cancer patients during COVID-19 pandemic were included. Results: At first 1,410 articles, were included in the study. After removing duplicate articles and reviewing the title and abstract, 55 articles were selected for the review. The findings of this study revealed COVID-19 greatly affects psychological health of cancer patients. Fear of COVID-19, fear of disease progression, disruption of oncology services, cancer stage, and immunocompromised status were the most common causes of psychological distress in oncology patients which can influence patients' decisions about treatment. Conclusion: The COVID-19 related anxiety is an expected reaction to the current situation. Although psychological distress affects many people, it can confuse cancer patients to the point that they refuse to continue treatment for the fear of infection and worsening of their condition. Since the end of this pandemic is unknown, this action can endanger the health and prognosis of this group of patients, so it seems that using psychological interventions and intensive counseling in the current situation is one of the main priorities for cancer patients.